PERAN KEPALA DESA DILIHAT DARI ASPEK INFORMASIONAL DALAM PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR JALAN USAHATANI DI DESA TEWAH PUPUH KECAMATAN BENUA LIMA KABUPATEN BARITO TIMUR (JAPB, 2022)
Research on the role of the Village Head seen from the informational aspect in the implementation of farm road infrastructure development in Tewah Pupuh Village, Benua Lima Subdistrict, East Barito Regency is important to do, because there are still several obstacles found in the implementation of farm road infrastructure development in what has been implemented so far, one of which is namely from the role of the Village Head as a monitor, provider of information by providing information to subordinates about all matters related to road construction, and the role of the Tewah Pupuh Village Head as a spokesperson for the community. The purpose of this study was to identify and analyze the role of the village head from an informational perspective in the implementation of infrastructure development for farming roads in Tewah Pupuh Village, Benua Lima Subdistrict, East Barito Regency. This research uses a qualitative descriptive approach. Techniques for collecting data through an interview process accompanied by observation and documentation. Source of data in this study is to take 5 respondents, data analysis and measurement criteria. The results of this study indicate that the role of the village head seen from the informational aspect in the implementation of the infrastructure development for farming roads in Tewah Pupuh Village, Benua Lima Subdistrict, East Barito Regency, has played a significant role. Based on the results of the study, the role of the village head from monitoring indicators, informants, and spokespersons in planning and implementation activities played a significant role in the development of farming road infrastructure in Tewah Pupuh Village, Benua Lima Subdistrict, East Barito Regency. Keywords: Informational Role, Development Implementation